Disaster Management of the Regional Disaster Manajement Agency (BPBD) of Gunungkidul Regency in Drought- Phone Areas - Kumalasari, Diah; Nurlukman, Adie Dwiyanto; Aditya, Toddy; Setiawan, Slamet (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Gunungkidul Regency experiences a clean water crisis every year due to the prolonged dry season and the geological condition of the Gunungkidul region, which is dominated by karst mountains, so that rainwater that falls on the ground surface will immediately seep into the ground and then form underground rivers. This research aims to see how disaster management in drought-prone areas by the Regional Disaster Management Agency (BPBD) of Gunungkidul Regency. This research uses a qualitative method by conducting interviews and observations. The results of this study indicate that in the face of drought BPBD Gunungkidul Regency has carried out various disaster management activities consisting of pre-disaster stages which include mitigation, preparedness and warning activities by producing various activities of mapping disaster-prone areas, monitoring weather forecasts and the formation of Disaster Resilient Villages/Groves and Disaster Safe Education Unit Schools (SPAB), during disasters by providing clean water dropping assistance and post-disaster at this stage BPBD Gunungkidul Regency conducts activities, namely rehabilitation and reconstruction.